Gender differences in footwear characteristics between half and full marathons in China: a cross-sectional survey - Xia, Yuyu; Shen, Siqin; Jia, Sheng-Wei; Teng, Jin; Gu, Yaodong; Fekete, Gusztáv; Korim, Tamás; Zhao, Haotian; Wei, Qiang; Yang, Fan (Scientific reports, 2023)
There are concerns about the risk of injuries caused by marathons in China. Since male and female runners have different injury risks, gender differences in running shoe functionality should be further complemented. A supervised questionnaire survey of 626 marathon runners was collected. The questionnaire was categorized into four sections: (1) participant profile, (2) importance of shoe properties, (3) functional evaluation of shoe properties and (4) importance ranking of shoe properties. The Mann–Whitney U test, Fisher’s exact test of cross tabulation and Chi-square test, and two-way ANOVA were used to analyze the results of this survey. The significance level was set at P < 0.05. The full marathon participants were older than the half marathon participants. There was no gender difference in the importance of shoe features to elite runners. In addition, women are more concerned about upper elasticity and have higher requirements for running shoes than men. Women were more focused on injury prevention, while men were more focused on running performance. Heel cushioning was identified by all participants as the most important running shoe feature. There were no gender differences between elite players’ demand for running shoes, but significant gender differences were found between genders at other running levels.